Factors Affecting Willingness to Vaccinate COVID-19 in Pregnant Women in Manggarai Regency, East Nusa Tenggara, Indonesia - Halu, Silfia Angela Norce; Dafiq, Nur; Banul, Maria Sriana; Laput, Dionesia Octaviani; Trisnawati, Reineldis E. (Journal of Maternal and Child Health, 2022)
Background: The COVID-19 vaccination has been recommended by WHO and the Ministry of Health of the Republic of Indonesia. Vaccination is carried out by pregnant women starting from the age of 13 weeks. Vaccines are expected to reduce the risk of pregnant women exposed to COVID-19. However, participation in receiving the COVID-19 vaccine in Manggarai Regency is still low. The purpose of this study was to analyze the factors that influence the willingness to vaccinate against COVID-19 in pregnant women in Manggarai Regency Subjects and Method: This was an analytic observational study with a cross-sectional design approach. This study was conducted in Manggarai Regency, East Nusa Tenggara, from January to May 2022. The sample in this study was 65 pregnant women who had never been vaccinated against COVID-19 with purposive sampling technique. The dependent variable in this study is the willingness of the vaccine. The independent variables are knowledge about COVID-19, knowledge about COVID-19 vaccination, belief, safety, effectiveness and side effects of COVID-19. Data collection using questionnaires and data processing using logistic regression analysis Results: Vaccination willingness was strongly influenced by mother's knowledge about COVID-19 in pregnancy (b=0.046; 95% CI= 0.003 to 0.73; p= 0.031), belief in the COVID-19 vaccine (b= 0.044; CI 95%= 0.003 to 0.757; p= 0.169), vaccination safety (b= 0.048; 95% CI= 0.004 to 0.639; p= 0.022). there was no significant effect, namely knowledge of vaccines (b= 0.195; 95% CI = 0.019 to 2.007; p=0.169) and vaccine effectiveness (b= 0.470; 95% CI= 0.048 to 0.4578; p=0.516). Conclusion: Vaccination willingness was strongly influenced by mother's knowledge about COVID-19 in pregnancy, belief in the COVID-19 vaccine and vaccination safety. Keywords: covid-19, vaccine, factor Correspondence: Silfia Angela Norce Halu. Diploma III of Midwifery, Universitas Katolik Indonesia Santu Paulus Ruteng, Manggarai, East Nusa Tenggara, Indonesia. Email: occe.halu@gmail.com. Mobile: 081259163953.